Mutations in PCDH21 cause autosomal recessive cone-rod dystrophy. Issue 10 (30th August 2010) - Ostergaard, E; Batbayli, M; Duno, M; Vilhelmsen, K; Rosenberg, T
Abstract : Background: Cone-rod dystrophy is a retinal dystrophy with early loss of cone photoreceptors and a parallel or subsequent loss of rod photoreceptors. It may be syndromic, but most forms are non-syndromic with autosomal dominant, autosomal recessive or X-linked recessive inheritance. Methods and results: We identified a small consanguineous family with six patients with cone-rod dystrophy from the Faroe Islands. Homozygosity mapping revealed a single homozygous locus of 4.2 Mb on chromosome 10q23.1–q23.2, encompassing 11 genes. All patients were homozygous for a 1-bp duplication in PCDH21, c.524dupA, which results in a frameshift and a premature stop codon (p.Q175QfsX47). Conclusion: To our knowledge, this is the first report of mutations in PCDH21 as a cause of human disease. PCDH21 is highly expressed in the retinal photoreceptor cells. It encodes protocadherin 21, which belongs to the cadherin superfamily of large cell surface proteins characterised by a variable number of extracellular cadherin domains. A PCDH21 knockout mouse model has previously shown loss of photoreceptor cells and abnormal cone and rod function, similar to the findings in the patients.